MONITORING PERFORMANCE OF LATERITE BASE TRIAL SECTION: A CASE OF ADDIS ABABA, ETHIOPIA - Alemgena ARAYA (Journal of Construction Project Management and Innovation)
This paper is aimed to present an overview of the provision of a demonstration/research trials with particular reference to pavement performance of a laterite base under a double bituminous surface treatment (DBST) as part of a long-term pavement performance (LTPP) monitoring in Ethiopia. The research components were aimed at increasing the use of locally available materials and solving specific problems related to the performance of some roads constructed with thin asphalt seals. In Ethiopia, most roads are built using crushed rock for road base. The project aim was to demonstrate that whether laterite can be used for base course, assess and evaluate the effect of sealed and unsealed shoulder in cut and fill sections. Out of the various field data measurements carried out in each monitoring period (wet and dry season) the paper reviews the in-situ dynamic cone penetrometer (DCP) test results and visual condition assessment observations. It is demonstrated that for such low volume roads laterite base trial sections are performing well, however DCP test results in these sections reveals that the crushed base control sections perform slightly better than the laterite base trial sections and the sections in cut are stronger than in fill while the shoulder sealing doesn’t provide consistent effect on the layer strengths.